An exploratory evaluation of the Emotional Literacy Support Assistant (ELSA) project - Haigh, Holly (2019)
The current thesis presents an exploratory evaluation of the Emotional Literacy Support Assistant (ELSA) project in primary schools. The ELSA intervention aims to improve schools’ capacity to support children with emotional literacy needs by training Teaching Assistants to equip them with the skills, knowledge and resources needed to support the social and emotional learning of children. Existing literature indicates a positive foundation of the intervention. However, due to the small body of research evaluating the ELSA project, and limitations to the existing evidence-base, the need for further research has been acknowledged. Therefore, the current study aimed to ascertain the measurable impact of ELSA support, as well as establish any perceived intervention effect. Factors viewed contributory to the positive impact of the intervention were also explored.